Complex indirect carotid-cavernous fistula with contralateral ophthalmic manifestations - Mohammad Razali, Amirah; Sobri, Mohammad Jazli; Fuad, Muhammad Khairul Adha; Abdul Rashid, Anna Misyail; Md Noh, Mohamad Syafeeq Faeez (Springer Science and Business Media LLC, 2024)
A carotid-cavernous fistula (CCF) involves an abnormal communication between the carotid artery and the cavernous sinus. For indirect CCF, it usually occurs in post-menopausal women. Contralateral symptoms for indirect CCF are rare. We report a 79-year-old lady with underlying hypertension and dyslipidemia, who had a complex indirect CCF from the right internal and right external carotid artery, draining into the left ophthalmic vein and giving rise to left ocular manifestation. Endovascular embolization was attempted but was unsuccessful. The patient subsequently developed a stroke one day post-procedure, with a favorable recovery of function.